Pengaruh Penggunaan Media Audio Visual terhadap Motivasi belajar PAK siswa kelas X - Nababan, Lilis Samsia (IAKN Tarutung, 2020)
This study aims to determine the positive and significant influence between the use audio visual media on the motivation of students studying Christian Religious Education Class X State Senior High School 2 Siborongborong North Tapanuli Regency 2019/2020 Academic Year, with a hypothesis there is a positive and significant effect between the use of media Audiovisual Learning Motivation for Christian Religious Education Class X State Senior High School 2 Siborongborong North Tapanuli Regency 2019/2020 Academic Year.This study uses a descriptive quantitative inferential approach, with a population of all students of class X Middle School 2 Siborongborong totaling 300 people with a sample of 42 people. Data were collected by 30 closed questionnaires compiled by the author based on variable indicators according to expert theory. The questionnaire trial was conducted on 30 students who were not research respondents, and had tested its validity and reliability. The results of data analysis show that there is a positive and significant influence between the use of audiovisual media on the learning motivation of Christian religious education in class X students of SMA Negeri 2 Siborongborong, North Tapanuli Regency in the 2019/2020 academic year with a coefficient of determination (= 38.06% and a significant test of influence is obtained 24.15 4.08, meaning Ho is rejected and Ha is accepted. Keywords: audio visual media, Christian Religious Education Learning Motivation